Metallic vaginal ring pessary: A rare entity - Uprety, UK; Regmi, MC; Budhathoki, B; Tiwari, RR; Subedi, S; Chhetri, S (Kathmandu University Medical Journal, 2009)
Vaginal pessaries still have role in the management of uterovaginal prolapse especially in elderly women, unfit for surgery and as a temporary relief for women waiting for surgery. Forgotten vaginal pessaries may cause serious complications. We here by present a case with metallic vaginal ring pessary for 16 years without significant symptoms. Key words: Prolapse, Ring pessary, Metallic pessary     doi: 10.3126/kumj.v6i4.1745     Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 508-510